Metode Studi Akidah dan Akhlak - Andre Nova Frarera, Mariyati,; Mariyati Mariyati; Sri Rahmayani Manalu; Ali Imran Sinaga (Jurnal Dirosah Islamiyah, 2023)
Islam has a very broad scope of study, among which the most important is the understanding of the creed and its implementation on moral development from it. This paper aims to analyze the methods in the study of faith and morality within the scope of Islam. Development of writing materials using the literature study method from related reference sources in order to enrich the body of knowledge on the study of faith and morality along with the method of approach. Based on this study, it was found that in understanding the study of aqeedah and morals, the steps in choosing a method and the accuracy of its use are determining factors for success in deepening the study of Islamic aqeedah and morals. Keywords: study; method; creed; morals